Between a sea of garbage and the new treatment plant: historical memoir and educational experiences for the administrative dilemma of solid waste in Río Azul, Costa Rica. - Bonilla, Leonardo (2016)
This article analyses the negative implications due to the operation of the sanitary landfill and the new treatment plant at Rio Azul, in La Union, Cartago, Costa Rica. The paper also refers the successful teaching experience of implementing an educational action project in the local school and community.  Therefore, the objective focuses on making visible the reasons for opening and closing the landfill, as well as on the social and environmental damages still present on the memory of inhabitants, and these prejudices can be inherited to the new generations with resilient objectives. Through a critical environmental education, it is possible to consider the contradictions in the waste management, from the administrative point of view, of the Costa Rica State, and the damage caused to the society and the environment. Issues being repeated with some peculiar nuances in several Costa Rican communities.